Quartz Enhanced Conductance Spectroscopy for Polymer Nano-Mechanical Thermal Analysis - Shangzhi Li; Bo Sun; Zhijin Shang; Biao Li; Ruyue Cui; Hongpeng Wu; Lei Dong (Applied Sciences, 2020)
A fast and highly sensitive polymer nano-mechanical thermal analysis method for determining the melting temperature (Tm) of polymer microwires was proposed. In this method, a small-size, low-cost quartz tuning fork was used as a piezoelectric transducer to analyze the thermodynamics of polymer microwires at the nanogram level without changing its own properties. Due to the thin wire sample, which has a length of 1.2 mm and a diameter of ~5 µm, which is bridged across the prongs of the tuning fork, the nanogram-level sample greatly reduces the thermal equilibrium time for the measurement, resulting in a fast analysis for the melting temperature of the polymer sample. Compared with the traditional method, the analysis method based on the quartz enhanced conductivity spectrum (QECS) does not require annealing before measurement, which is an essential process for conventional thermal analysis to reduce the hardness, refine the grain, and eliminate the residual stress. In this work, the melting temperatures of three of the most commonly used polymers, namely polymers polymethyl methacrylate, high-density polyethylene, and disproportionated rosin, were obtained under the temperature from room temperature to >180 °C, proving the QECS method to be a useful tool for nano-mechanical thermal analysis.